2021
DOI: 10.24875/ric.19003250
|View full text |Cite
|
Sign up to set email alerts
|

Brain Gene Expression-DNA Methylation Correlation in Suicide Completers: Preliminary Results

Abstract: Background: Gene expression alterations have been implicated in suicide pathology. However, the study of the regulatory effect of DNA methylation on gene expression in the suicidal brain has been restricted to candidate genes. Objective: The objective of the study was to identify genes whose expression levels are correlated with DNA methylation in the prefrontal cortex of suicides. Methods: Postmortem prefrontal cortex samples from 21 suicides and six non-suicides were collected. Transcriptomic and DNA methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…This altered gene expression of SSAT1 would be expected when there is homeostatic disruption, causing increases in spermine levels, spermidine levels, or both. Additionally, an analysis of transcriptomic and DNA methylation profiles of 21 individuals who died by suicide showed that polyamine oxidase (PAOX) gene expression is up-regulated, which provides a better explanation of the altered levels of polyamines in the brain of completed suicide [ 63 ]. Together, these findings suggest that changes in polyamine levels may have deep effects, due to the multiple processes that polyamines contribute to in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…This altered gene expression of SSAT1 would be expected when there is homeostatic disruption, causing increases in spermine levels, spermidine levels, or both. Additionally, an analysis of transcriptomic and DNA methylation profiles of 21 individuals who died by suicide showed that polyamine oxidase (PAOX) gene expression is up-regulated, which provides a better explanation of the altered levels of polyamines in the brain of completed suicide [ 63 ]. Together, these findings suggest that changes in polyamine levels may have deep effects, due to the multiple processes that polyamines contribute to in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Complementary studies found different methylation levels in the PFC of suicide victims [222,223]. Interestingly, Cabrera-Mendoza and colleagues found a significant correlation between 22CpGs and gene expression in suicide victims [224].…”
Section: Dna Methylation Alterations In the Brain From Postmortem Stu...mentioning
confidence: 98%
“…There are multiple approaches to analyse DNA methylation on a genome-wide scale, including whole genome bisulphite sequencing and microarray and antibody-based approaches; these can again make it hard to directly compare studies[ 34 ]. The results defined a complex picture of the association of DNA methylation and suicidal behaviour, which included the involvement of differences in cognitive functions[ 35 ], cell cycle and cell-cell signalling[ 36 , 37 ], regulation of gene transcription and expression[ 38 ], glutamate signalling[ 39 ], cell structural integrity and nervous system regulation[ 40 ], and neurodevelopment and polyamine metabolism[ 41 ].…”
Section: Use Of -Omics In Research Into Suicidal Behaviourmentioning
confidence: 99%